Chemotaxis: moving forward and holding on to the past - Bagorda, Anna; Mihaylov, Vassil A.; Parent, Carole A. (Thrombosis and Haemostasis, 2006)
The ability of cells to sense external chemical cues and respond by directionally migrating towards them is a fundamental process called chemotaxis. This phenomenon is essential for many biological responses in the human body, including the invasion of neutrophils to sites of inflammation. Remarkably, many of the molecular mechanisms involved in controlling neutrophils chemotaxis arose millions of years ago in the simple eukaryotic organism Dictyostelium discoideum. Both neutrophils and Dictyostelium use G protein-coupled signaling cascades to mediate chemotactic responses, which are responsible for transducing external cues into highly organized cytoskeletal rearrangements that ultimately lead to directed migration. By using the genetically and biochemically tractable organism Dictyostelium as a model system, it has been possible to decipher many of the signal transduction events that are involved in chemotaxis.
Keywords: Dictyostelium; neutrophils; chemotactic signaling